Psychology & behavioral health Volume 3 Hearing - Parental alienation syndrome - Moglia, Paul (Ipswich, Massachusetts Salem Press, 2015)
Provides a comprehensive five-volume set that covers notable theories, people, social issues, life stages, the physiology and anatomy of the nervous system, and various mental illnesses or conditions, all in a simple, easy to use A-Z format
volume 3. Hearing-Parental alienation syndrome
Previously published as: Psychology & mental health.
This set covers not only the history of the field and the core aspects of behaviorism, cognitive psychology, and psychoanalytic psychology, but also diagnoses, disorders, treatment, assessment, and notable individuals in the field.
102713
Keywords: Psychology, Applied; Mental health; Mental illness; Medicine and psychology